Development of ductal carcinoma of the pancreas during follow-up of branch duct intraductal papillary mucinous neoplasm of the pancreas. Issue 11 (13th May 2008) - Uehara, H; Nakaizumi, A; Ishikawa, O; Iishi, H; Tatsumi, K; Takakura, R; Ishida, T; Takano, Y; Tanaka, S; Takenaka, A
Abstract : Background: Synchronous occurrence of intraductal papillary mucinous neoplasm (IPMN) and ductal carcinoma of the pancreas has been reported. Branch duct IPMNs with lower likelihood of malignancy are not submitted to resection but are followed-up, so ductal carcinoma may develop during the follow-up. The development of ductal carcinoma of the pancreas during follow-up of branch duct IPMNs was investigated. Methods: 60 patients with branch duct IPMN who had an intraductal tumour of <10 mm on imaging examinations and a negative result for malignancy on cytological examination of the pancreatic juice were investigated. They were followed-up mainly by ultrasonography (US), and additionally by endoscopic ultrasonography (EUS), CT, magnetic resonance cholangiopancreatography (MRCP) or endoscopic retrograde cholangiopancreatography (ERCP) with cytological examination of the pancreatic juice for an average period of 87 months. Results: Ductal carcinoma of the pancreas distinct from IPMN developed in 5 of 60 (8%) branch duct IPMNs during follow-up. The 5-year rate of development of ductal carcinoma was 6.9% (95% CI 0.4% to 13.4%), the incidence of ductal carcinoma was 1.1% (95% CI 0.1% to 2.2%) per year and the standardised incidence ratio of development of ductal carcinoma was 26 (95% CI 3 to 48). Patients >70 years old developed ductal carcinoma significantly more frequently than those under 69. Four of five ductal carcinomas identified during follow-up were resectable. Cancer developed in IPMN in 2 of 60 (3%) branch duct IPMNs during follow-up. Conclusions: During follow-up of branch duct IPMNs, ductal carcinoma of the pancreas not infrequently developed distinct from IPMN. In the follow-up of IPMN, special attention should be paid to the development of ductal carcinoma of the pancreas.